Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.15294/biosaintifika.v9i2.8972
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Gills and Liver Histological Structure of Cyprinus carpio L. Exposed to Leachate

Abstract: One of the main problems in the waste management in Indonesia is the treatment of leachate, which mostly dumped to the river This research is aimed to obtain information of histological alteration in gills and liver of C. carpio L. exposed to leachate. Measurements on the water quality parameters comprised water temperature, pH, and dissolved oxygen (DO). This research was conducted by exposing leachate to C. carpio for 96 hours. The concentration of leachate were 0 ppm, 80 ppm, and 100 ppm. Histological prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…This result supports several observations which reported that fish exposed to Cd, Cu, Fe, Pb, Mn and Zn and other heavy metals and contaminants resulted in histopathological changes (Randi, Monserrat, Rodriguez, & Romano, 1996). This result is also similar to the report of Pribadi, Syahidah, Harjanti, and Malini (2017) on Cyprinus carpio exposed to leachate. Severe necrosis observed at higher concentration of leachate might have resulted from the effort to get rid of the toxicant and the failed attempt to regenerate new cells.…”
Section: Changes In Haematological Parameters Of C Gariepinussupporting
confidence: 92%
“…This result supports several observations which reported that fish exposed to Cd, Cu, Fe, Pb, Mn and Zn and other heavy metals and contaminants resulted in histopathological changes (Randi, Monserrat, Rodriguez, & Romano, 1996). This result is also similar to the report of Pribadi, Syahidah, Harjanti, and Malini (2017) on Cyprinus carpio exposed to leachate. Severe necrosis observed at higher concentration of leachate might have resulted from the effort to get rid of the toxicant and the failed attempt to regenerate new cells.…”
Section: Changes In Haematological Parameters Of C Gariepinussupporting
confidence: 92%
“…Lamellar fusion is likely caused by lamella hyperplasia (Carvalho et al, 2020). This is also assumed to indicate cell degeneration and eventually a sign of early necrosis (Pribadi et al, 2017). Hyperplasia is characterized by enlargement of the epithelium due to an increasing number of cells that cause dilation on the lamellae; therefore, lamellar fusions were occurred (Figure 2).…”
Section: Tissue Alterationmentioning
confidence: 99%